2018
DOI: 10.24015/japm.2017.0050
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Procedure Neuraxial Ultrasound in Obstetric Anesthesia

Abstract: Aim of review:To determine the current state of pre-procedure neuraxial ultrasound in obstetric anesthesia practice. Methods: The PubMed and Scopus databases were searched for the keywords "neuraxial", or "epidural", or "spinal" or "ultrasound", combined with "obstetric anesthesia". A current review of original studies, systematic reviews, and meta-analysis within the past decade were included in the analysis. Recent findings: Pre-procedure ultrasound imaging enhances successful neuraxial placement through det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Vallejo et al . [ 17 ] in a prospective randomized nonblinded study randomized 370 parturient requesting labor epidural analgesia to receive their epidural by first-year anesthesia residents with or without prior ultrasound determination of epidural space depth. They found that the incidence of epidural catheter replacement for failed analgesia was fewer in the ultrasound group and the number of attempts and accidental dural punctures were also lesser in ultrasound group when compared to palpatory group.…”
Section: Discussionmentioning
confidence: 99%
“…Vallejo et al . [ 17 ] in a prospective randomized nonblinded study randomized 370 parturient requesting labor epidural analgesia to receive their epidural by first-year anesthesia residents with or without prior ultrasound determination of epidural space depth. They found that the incidence of epidural catheter replacement for failed analgesia was fewer in the ultrasound group and the number of attempts and accidental dural punctures were also lesser in ultrasound group when compared to palpatory group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, obese patients are more likely to experience a longer procedure time, a higher incidence of accidental dural puncture, a higher incidence of epidural venous puncture, and higher overall failure and complication rates during neuraxial anesthesia placement. [ 76 77 ] Neuraxial US (pre-procedural or real-time) can be used to identify the intervertebral space(s), the midline for insertion, determine the depth from the skin to the epidural space, the best needle insertion point, and the best angle for needle insertion. [ 77 ] This leads to decrease of the number of attempts required for epidural placement, the risk for epidural hematoma, and post-surgical low back pain.…”
Section: Regional Analgesiamentioning
confidence: 99%
“…[ 76 77 ] Neuraxial US (pre-procedural or real-time) can be used to identify the intervertebral space(s), the midline for insertion, determine the depth from the skin to the epidural space, the best needle insertion point, and the best angle for needle insertion. [ 77 ] This leads to decrease of the number of attempts required for epidural placement, the risk for epidural hematoma, and post-surgical low back pain. [ 77 ] The use of pre-procedural US imaging has shown a higher first-attempt success rate for epidural catheter placement, less need for needle repositioning, which leads to shorter total procedure time.…”
Section: Regional Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound guided placement (US) could be a method of improving speed of placement of neuraxial analgesia as it provides an opportunity to directly visualize landmarks which have traditionally been located by palpation. US guidance for regional anesthesia has gained tremendous popularity over the past 15 years [5][6][7][8]. In a literature review published in 2016 by Soni et al, 20 randomized trials and 2 meta-analysis comparing landmark-based versus ultrasound-guided techniques for lumbar puncture or epidural/spinal anesthesia, showed a large advantage of the US technique in different patient populations, using different outcomes (see Table 1) [9].…”
Section: Introductionmentioning
confidence: 99%